The Importance Of Finding Out Factors That Can Trouble The Musculo-Ligamentar Equilibrium In Pacients With Complete And Extended Partial Edentation - D.N. Bosanceanu; Silvia Mihaela Silvas; Dana Gabriela Budala; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2011)
The stomatology of the third millenium acquired new boundries and dimensions, upshot of the developement of the diagnosis and therapy, they themselves being influenced by the modern and complex technology and also by the psycho-social and communication aspects. The functionality of the stomatognat system depends on many factors which can act on it in the direction of equilibrum and that can anytime be changed, adapting to new situations and circumstances. Among the elements that play a role in the stomatognat system'stability, a special place is held by the muscular factor, the dynamic constituent.